2019
DOI: 10.3390/ijerph16010125
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Status of Health Service Utilization among 3–5 Years Old Left-Behind Children in Poor Rural Areas of Hunan Province, China: A Cross-Sectional Survey

Abstract: The left-behind children (LBC) in China generally refer to children who remain in rural regions under the care of kin members while their parents migrate to urban areas. Due to some reasons, e.g., poverty, poor transportation conditions, lack of health resources, and preschool child care, it is hard for preschool-aged rural LBC to obtain essential health services. Random cluster sampling was used to recruit the caregivers and all the 3–5-year-old LBC in two rural counties in Hunan Province. A questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, most preschool-aged LBC in China are scattered in poor rural areas without LBC care institutions, such as kindergartens, making it difficult for the country’s existing basic public health service policies and related mental health interventions to benefit this vulnerable group. This study also found that the utilization of health services by LBC and their caregivers in poor rural areas was extremely low [2,3].…”
Section: Introductionmentioning
confidence: 98%
“…However, most preschool-aged LBC in China are scattered in poor rural areas without LBC care institutions, such as kindergartens, making it difficult for the country’s existing basic public health service policies and related mental health interventions to benefit this vulnerable group. This study also found that the utilization of health services by LBC and their caregivers in poor rural areas was extremely low [2,3].…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, the number of left-behind children in rural areas has increased markedly. A national survey in 2013 reported 61.025 million left-behind children [3], most of whom were raised by elderly caretakers. Low education levels, economic disadvantages and irresponsible child supervision all contributed to the alarmingly high incidence rate of eye injuries among rural children, with percentages as high as 46.7-48.1% [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Children aged 3–6 years have acquired their preliminary independence and initiative, and are gradually learning to eat independently, which is the best stage for them to develop sound eating behaviours. Separated from their parents during this period, especially their mothers, children are more likely to have externalised developmental problems and internalised emotional problems than those who live with their parents (Liu, Yang, et al., 2018; Ouyang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%